2020
DOI: 10.1097/aci.0000000000000634
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and epigenetics of allergy

Abstract: Purpose of review Allergic diseases are prototypic examples for gene × environment-wide interactions. This review considers the current evidence for genetic and epigenetic mechanisms in allergic diseases and highlights barriers and facilitators for the implementation of these novel tools both for research and clinical practice. Recent findings The value of whole-genome sequencing studies and the use of polygenic risk score analysis in homogeneous well c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 82 publications
0
15
0
1
Order By: Relevance
“…GC is a sustained multistep process that involves accumulated genetic damage, altered epigenetic signatures, and exposure to environmental factors. An increasing number of studies have confirmed that epigenetic alterations can mediate the effects of environmental factors on disease ( Agache et al, 2020 ). As the most typical epigenetic alteration, DNA hypermethylation is closely linked to improper transcriptional silencing and the functional loss of genes to accelerate the growth of tumor cells and promote tumorigenesis and development ( Abudurexiti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…GC is a sustained multistep process that involves accumulated genetic damage, altered epigenetic signatures, and exposure to environmental factors. An increasing number of studies have confirmed that epigenetic alterations can mediate the effects of environmental factors on disease ( Agache et al, 2020 ). As the most typical epigenetic alteration, DNA hypermethylation is closely linked to improper transcriptional silencing and the functional loss of genes to accelerate the growth of tumor cells and promote tumorigenesis and development ( Abudurexiti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes can be mitotically (cellular memory) or meiotically (parental imprinting) heritable and can be passed through generations 28 . Interestingly, already the prenatal and early postnatal period can influence the development of diseases such as allergy in adulthood 28,29 . Several recent, epigenomic studies in the field of allergic diseases allowed identification of epigenetic signatures of asthma/allergy and are summarized in Table 50–57 .…”
Section: Basic Omics Strategiesmentioning
confidence: 99%
“…The human genes involved in IgE response include those controlling the IgE locus and those encoding the HLA class II complex favoring the expansion of allergen‐specific Th2 cells and the IgE switch of B cells. These genes are located in the chromosome (chr) 5 (region 5q23‐35) encoding type‐2 cytokines, chr6 encoding HLA class II alleles and the peptide transport molecules TAP1 and TAP2, chr11 for the high‐affinity Fcε receptor (FcεRI), chr12 for the signal transducer and activator of transcription 6 (STAT6), and chr16 for the IL‐4R α‐chain 24‐26 . Several polymorphisms associated with candidate genes for respiratory allergy have been described, which may vary according to racial diversity 27 .…”
Section: Genetic and Epigenetic Factors Contribute To The Development...mentioning
confidence: 99%
“…These genes are located in the chromosome (chr) 5 (region 5q23-35) encoding type-2 cytokines, chr6 encoding HLA class II alleles and the peptide transport molecules TAP1 and TAP2, chr11 for the high-affinity Fcε receptor (FcεRI), chr12 for the signal transducer and activator of transcription 6 (STAT6), and chr16 for the IL-4R α-chain. [24][25][26] Several polymorphisms associated with candidate genes for respiratory allergy have been described, which may vary according to racial diversity. 27 The principal well-documented genes involved in the genetic alterations in these diseases are listed in Table 1.…”
Section: G Ene Ti C and Epi G Ene Ti C Fac Tor S Contribute To The De...mentioning
confidence: 99%